Early developmental, temperamental and educational problems in 'substance use disorder' patients with and without ADHD. Does ADHD make a difference?. (December 2015) - Skutle, Arvid; Bu, Eli Torild Hellandsjø; Jellestad, Finn Konow; van Emmerik-van Oortmerssen, Katelijne; Dom, Geert; Verspreet, Sofie; Carpentier, Pieter Jan; Ramos-Quiroga, Josep Antoni; Franck, Johan; Konstenius, Maija; Kaye, Sharlene; Demetrovics, Zsolt; et al.
Abstract: Introduction: The prevalence of ADHD among patients with substance use disorder (SUD) is substantial. This study addressed the following research questions: Are early developmental, temperamental and educational problems overrepresented among SUD patients with ADHD compared to SUD patients without ADHD? Do this comorbid group receive early help for their ADHD, and are there signs of self-medicating with illicit central stimulants? Method: An international, multi-centre cross-sectional study was carried out involving seven European countries, with 1205 patients in treatment for SUD. The mean age was 40 years and 27% of the sample was female. All participants were interviewed with the Mini International Neuropsychiatric Interview Plus and the Conners' Adult ADHD Diagnostic Interview for DSM-IV. Results: SUD patients with ADHD ( n = 196; 16.3% of the total sample) had a significantly slower infant development than SUD patients without ADHD ( n = 1, 009; 83.4%), had greater problems controlling their temperament, and had lower educational attainment. Only 24 (12%) of the current ADHD positive patients had been diagnosed and treated during childhood and/or adolescence. Finally, SUD patients with ADHD were more likely to have central stimulants or cannabis as their primary substance of abuse, whereas alcohol use was more likely to be the primary substance of abuse in SUD patients without ADHD. Conclusion: The results emphasize the importance of early identification of ADHD and targeted interventions in the health and school system, as well as in the addiction field. Highlights: SUD patients with ADHD had a significantly slower infant development than SUD patients without ADHD. Furthermore, the former group had greater problems controlling their temperament, and had lower educational attainment. Only 12% of the current SUD and ADHD patients had been diagnosed and treated during childhood and/or adolescence. They were more likely to have stimulants or cannabis as their main substance, suggesting some form of self-medication. Early identification of ADHD is important, as well as adequate treatment of this comorbid patient group.